ANALYSIS OF THE PROBLEM OF SOLVING THE PROBLEM IN COMPLETING THE PROBLEM OF THE STORY BASED ON THE STEPS OF THE PATTERN IN COMPARATIVE MATERIAL - Sinambela, Mindo Hotmaida (JURNAL EDUSCIENCE (JES), 2020)
Each student has different abilities in problem solving, especially in story problems. Haji (1994: 13) suggests that questions that can be used to determine students' abilities in the field of mathematics study can take the form of story problems. The purpose of this research is to describe the ability of students to solve mathematical problems in solving comparative story problems based on Polya'sÂ steps. This research is a descriptive study using a qualitative approach. Three (3) subjects were taken from students of class VIIA at SMP Negeri 1 Wamena consisting of one high ability student, one medium ability student, and one low ability student. Retrieval of data taken by the test and interview methods. The test used was in the form of a description test of three (3) questions. Based on the research results obtained: the ability to solve mathematical problems in High Ability Students (SKT) can do all the problem solving comparative story problems based on Polya steps, while the Medium Ability Students (SKS) there are two questions that have not fully taken Polya's steps specifically implementing the completion plan and check again. For Low Ability Students (SKR) almost all the questions given cannot be solved using Polya steps.Keywords: Problem solving, Polya steps, comparison problems.